Groove and Percussion in the Music Classroom. (September 2022) - Smith, Gareth Dylan
In this article, I explain how percussion and groove are at the core of many musics created and enjoyed today, yet they can be overlooked in music teaching and learning. A pervasive culture of pitched-instrument prejudice makes it difficult to take rhythm and groove seriously, although these can be at the core of meaningful music-making experiences in schools. I provide an original, flexible composition for nonpitched percussion, with easy-to-follow instructions and video demonstration. The article invites teachers to consider embracing an engaging, Afrological approach to making music that emphasizes feel and groove.